Steel bridge strengthening a study of assessment and strengthening experience and identification of solutions - Kennedy Reid, Iain L. (Thomas Telford, 2001)
The stresses imposed on UK roads by forty tonne vehicles have led to an extensive programme of bridge improvements across the country. This book draws on case studies to create an essential tool for all bridge engineers involved in strengthening steel bridges to meet these challenges.